Encyclopedia of knowledge management - Schwartz, David G.; Thomson Gale (Firm) (Hershey, Pa. : Idea Group Reference, 2006)
"This encyclopedia is a research reference work documenting the past, present, and possible future directions of knowledge management"--Provided by publisher.
Includes bibliographical references and index.
Elektronická reprodukce.
Keywords: Knowledge management; Information resources management; Information networks -- Management; Organizational learning